Price formation in financialized commodity markets : the role of information (United Nations New YorkUS, 2011)
Aims to provide comprehensive insights into recent developments in the functioning of commodity markets. Pays particular attention to information flows that affect trading decisions. Focuses on six commodities - crude oil, barley, cocoa, maize, sugar and wheat.
References p. 63-65.